Perioperative Nursing Rounds : Bladder Neck Suspension - Lawson, Wendy (Operating Room Nurses Association of Canada Journal, 1991)
The goal of this article is to share experience and knowledge as it was researched for Perioperative Nursing rounds at our hospital.